STRATEGI GURU DALAM MENANAMKAN KARAKTER DISIPLIN SISWA KELAS II MELALUI PEMBELAJARAN QIROATI DI SD SEMESTA BILINGUAL SCHOOL - Yasinta Nur Wahyuningtyas; Sundari, Riris Setyo; Duwi Nuvitalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Instilling the character of discipline in elementary school students, particularly within a bilingual school environment, is a challenge that warrants serious attention in educational practice. This research aims to describe teachers' strategies for instilling disciplinary character through Qiroati learning among second-grade students at SD Semesta Bilingual School, as well as to identify the influencing factors and its impact on students' disciplinary behavior. This study employs a descriptive qualitative approach. The research subjects included second-grade and Qiroati teachers, with the school principal and counselor serving as supporting informants. Data were collected through observation, interviews, and documentation studies, while data validity was verified using technical triangulation. The findings indicate that the cultivation of disciplinary character is implemented through several strategies: teacher modeling, consistent rule enforcement, the provision of educational rewards and sanctions, and collaborative discipline application. Regularly conducted Qiroati learning has proven effective in shaping students' disciplinary habits, as reflected in their punctuality, adherence to rules, and patience in waiting for their turn. Consequently, Qiroati learning makes a tangible contribution to fostering students' awareness of discipline through a direct process of habituation rather than coercion.